2012
DOI: 10.2528/pier12050304
|View full text |Cite
|
Sign up to set email alerts
|

Designing Asian-Sized Hand Model for Sar Determination at Gsm900/1800: Simulation Part

Abstract: Abstract-A simple geometrical Asian-hand model with human tissue properties posed at two common talk-mode positions is proposed for comparative study. The newly designed hand is formed by measuring an adult female hand at open-hand position before being posed into the presented styles. Four human hand tissues are included: skin, bone, muscle, and tendon, and also three homogeneous sets of hands using specific anthropomorphic mannequin (SAM) hand phantom dielectric properties. A candy-bar type mobile phone with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The simulated results are obtained using the full-wave electromagnetic field simulation software HFSS version [21][22][23][24][25][26][27][28]. In Figure 4(a), the simulated return loss (1000-2200 MHz) is presented when cited resonant effects on simulated return loss are shown (5.1-6.0 GHz, WLAN 11a).…”
Section: Antenna Design and Parametric Studymentioning
confidence: 99%
“…The simulated results are obtained using the full-wave electromagnetic field simulation software HFSS version [21][22][23][24][25][26][27][28]. In Figure 4(a), the simulated return loss (1000-2200 MHz) is presented when cited resonant effects on simulated return loss are shown (5.1-6.0 GHz, WLAN 11a).…”
Section: Antenna Design and Parametric Studymentioning
confidence: 99%
“…In the analysis of the characteristics of radiation in the range of 150 MHz to 1.2 GHz from inside the human body done by [23], it was suggested that frequencies between 450 MHz and 900 MHz provided maximum radiation from the ingested RF source. Using the human body model [24][25][26][27][28][29] in our previous work [10], we conducted an extensive investigation of the variation of path loss in the human body in terms of system frequency and variation of the location of the capsule. A summary of the results of our investigation are shown in Figure 1.…”
Section: Frequency Approachmentioning
confidence: 99%
“…However, this model only can provide a rough estimate of the path loss, which limits it applicability because more accurate estimates of path loss are required for simulations using the digital body model [30][31][32][33][34][35][36][37].…”
Section: Methods and Analysismentioning
confidence: 99%